Expression of Bcl-2 and p53 protein in Stomach Cancer Patients and Association with Clinicopathological Factors - Ramin Azarhoush; Roozbeh Cheraghali; Mohammad Sadegh Saffarian; Fatemeh Mehravar (Golestan University Of Medical Sciences, 2017)
Introduction: Stomach cancer is one of the most common cancers worldwide. Bcl-2 and p53 appear to be important biomarkers in patients with stomach cancer. In this study, we investigated the expression of Bcl-2 and p53 proteins and its association with clinicopathological factors in 67 Iranian stomach cancer patients over a 5-year period (2010-2015). Material and Methods: In this cross sectional study, the expression of the Bcl-2 and p53 protein was determined using immunohistochemistry, and the pathological features of tumors were evaluated. Results: The expression of Bcl-2 and p53 proteins was detected in 47% and 48% of the patients, respectively. Of the 67 patients, 39 patients had intestinal-type gastric adenocarcinoma, and 57 patients had grade І and ΙΙ. There was a statistically significant association between Bcl-2 and p53 expressions (P=0.04). Conclusions: There is an association between Bcl-2 and p53 protein expressions in patients with stomach cancer. Bcl-2 and p53 protein expressions are more frequent in high-grade tumors. Bcl-2 and p53 expression might play an important role in the early development and phenotypic differentiation of gastric carcinomas, but not so in tumor progression.